City networks' power in global agri-food systems - Partzsch, Lena; Luemmen, Jule; Löhr, Anne-Cathrine (Agriculture and Human Values, 2022)
Cities and local governments loom large on the sustainability agenda. Networks such as Fair Trade Towns International (FTT) and the Organic Cities Network aim to bring about global policy change from below. Given the new enthusiasm for local approaches, it seems relevant to ask to what extent local groups exercise power and in what form. City networks present their members as "ethical places" exercising power with, rather than power over others. The article provides an empirical analysis of the power of FTT and Organic Cities in Germany. In both cases, we found cities that are eager to emphasize their inclusive potential. Their willingness to compromise is demonstrated most illustratively by the fact that several cities are members of both networks: While the FTT campaign aims to address problems of international trade but does not abandon it, Organic Cities advocate for a new localism based on food supply from farmers in the same region. In both cases, city networks use their purchasing power to increase the share of certified products. By doing so, the city networks reproduce privileged positions of consumers benefitting from the global capitalist order (power over). However, our analysis revealed that networks also make citizens reflect upon agri-food challenges and allow developing alternatives for more sustainable systems (power with).
CRIS-Team WoS Importer:2022-04-08